Pengaruh Kompensasi dan Motivasi terhadap Kinerja Pegawai di Kantor Kelurahan Langkai Kota Palangka Raya - Siren Siren; Andrea Oktaviani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
This study aims to determine how much influence Compensation and Motivation has on Employee Performance in Langkai Village Office, and can find out which variables are most dominant in influencing Employee Performance. The type of research used is quantitative. The sample taken in the study saw a relatively small number of staff so that the entire population was used as samples called saturated samples. Where saturated samples are sampling techniques if all members of the population are used as samples. Data collection techniques with the questionnaire method. The questionnaire or questionnaire method according to Purwito is